Current perspectives and trends in acupuncture for sleep disorders: a bibliometric analysis - Huang, Yi; Ying, Xihan; Zhang, Jieqi; Hu, Rong; Chen, Yi; Wu, Lei; Chen, Bowen; Zhang, Kai; He, Kelin; Ma, Ruijie (Frontiers in Psychiatry, 2024)
Background Limitations of conventional treatment methods for sleep disorders have driven the use and development of complementary and alternative therapies such as acupuncture. However, despite the surge in related studies, there is still a lack of visual analysis and detailed elaboration regarding the current status, international collaborations, and research hotspots of acupuncture for sleep disorders. Methods We conducted a bibliometric analysis of publications on acupuncture for sleep disorders using the Web of Science Core Collection database from 2004 to 2023. We utilized the R package “bibliometrix” to count publications and citations, VOSviewer to create an inter-institutional referencing network, and CiteSpace to identify references and keywords with the highest citation bursts. Additionally, we employed a bibliometric online analysis platform designed for analyzing national partnerships. Results A total of 432 pertinent papers were retrieved, with China being the most prolific contributor, accounting for 61.6% of the publications, followed by the United States and South Korea. Despite China’s high output, its average article citation rate and proportion of international collaborations were notably lower than those of the United States. Key research institutions such as the University of Hong Kong, Shanghai University of Traditional Chinese Medicine, Memorial Sloan Kettering Cancer Center, and Guangzhou University of Chinese Medicine have played significant roles in this field. Among authors, Ka-Fai Chung from the University of Hong Kong stood out as the most productive. In terms of journals, MEDICINE was the most active, while SLEEP was considered the most authoritative. The clinical effects of acupuncture for insomnia have garnered significant attention in recent years, with electroacupuncture emerging as the prevailing technique for addressing sleep disorders. Conclusion This bibliometric study effectively outlines the basic framework of knowledge surrounding acupuncture for sleep disorders over the past two decades, covering publications, countries, institutions, authors, and sources. It highlights promising clinical effects and underlying mechanisms of acupuncture, particularly for secondary insomnia and specific sleep disorders like restless legs syndrome. Moving forward, the focus and challenge for future research lie in the development of standardized study protocols and harmonization of efficacy assessment metrics.